Host–Guest Chemistry of Carboranes: Synthesis of Carboxylate Derivatives and Their Binding to Cyclodextrins. Issue 49 (26th July 2018) - Nekvinda, Jan; Grüner, Bohumír; Gabel, Detlef; Nau, Werner M.; Assaf, Khaleel I.
Abstract: Polyhedral carboxymethyl carborane (C2 B10 H12 ) derivatives, including mono‐ and disubstituted o ‐, m ‐, and p ‐isomers, have been synthesized. Supramolecular host–guest complexation of these derivatives with cyclodextrins (CDs; namely, α‐, β‐, and γ‐CD) has been investigated in water. The globular structure of the carborane binding moiety and its hydrophobic character qualify it as an ideal recognition site to form stable inclusion complexes with macrocyclic host molecules in aqueous solution. The measured binding affinities for the carborane derivatives were in the millimolar range ( K a =10 3 –10 4  m −1 ) with differently sized CDs, and preferential binding to β‐CD. Abstract : Filling the gaps : Polyhedral carboxymethyl carborane (C2 B10 H12 ) derivatives, including mono‐ and disubstituted o ‐, m ‐, and p ‐isomers, have been synthesized (see figure), so that their supramolecular host–guest complexation with cyclodextrins (α‐, β‐, and γ‐) could be investigated in water. Among the disubstituted carborane isomers, the para isomer showed a greater binding affinity; this might reflect more effective hydrogen‐bond formation between host and guest.